MANAGEMENT INFORMATION SYSTEMS & CUSTOMER DASHBOARD VSAT SERVICES IN PT XYZ - Zuliani, Erni; Dores, Ardiansyah (International Humanities and Applied Science Journal, 2018)
The development of Information Technology nowadays has caused a shif in a corporate’s standard of effectiveness and it has become a compulsory for its development. The new standard is in line with the need of information that is easy to get and efficiently. PT. XYZ is a national private company engaging in telecommunication network business, and focused on equipment supplying and telecommunication service based on Very Small Apperture Terminal (VSAT). In order to organize the project, PT. XYZ currently has not used the full information system. By using a Dashboard Management Information System, it is expected to help corporate’s to achieve an activity mechanism that is more effective and controlled that enables them to be implemented to ease the monitoring, managing the current project so that it can be well-organized.